Impact of prenatal alcohol exposure on neurodevelopmental outcomes: a systematic review. Issue 1 (31st December 2022) - Chu, Joanna Ting Wai; McCormack, Jessica; Marsh, Samantha; Wells, Alesha; Wilson, Holly; Bullen, Chris
ABSTRACT: Background: Prenatal exposure to alcohol (PAE) represents a significant public health concern. Previous research linking PAE to neurodevelopmental outcomes has been mixed and often has limited focus on residual confounding or moderating factors. Methods: A systematic review of prospective cohort studies ( n  = >1000) assessing the impact of PAE on neurodevelopmental outcomes was undertaken (neurophysiology, motor skills, cognition, language, academic achievement, memory, attention, executive function, affect regulation, and adaptive behaviour, social skills, or communication). Electronic searches of EMBASE, Medline, CINAHL, and Psychinfo were conducted in May 2021. A quality assessment was conducted using an adapted version of the Newcastle-Ottawa Scale (NOS). Results: Thirty longitudinal cohort studies met the inclusion criteria. Evidence of the impact of PAE was mixed across domains. We found no evidence that PAE affects executive function, but there were impacts on motor skills, cognition, language, academic achievement, attention, affect regulation, and adaptive behaviour. The most consistent adverse effect was on affect regulation (nine out of thirteen studies, six of which found an association between heavy alcohol consumption or binge drinking during pregnancy). We found no protective factors. Few studies controlled for variables in the postnatal environment. Discussion: This review was unable to conclude a safe level of alcohol consumption during pregnancy. Methodological improvements are needed to improve the quality and consistency in which PAE is studied. Further research into residual confounding variables is vital, including a greater focus on the postpartum environment.